TINJAUAN TERHADAP PERHITUNGAN, PENYETORAN DAN PELAPORAN PPH PASAL 21 ATAS GAJI KARYAWAN TETAP PADA PT. ACKIRA CIRA PERKASA - Hutahaean, Ita Purnama; Kennedy, Posma Sariguna Johnson (Fakultas Ekonomi Universitas Kristen Indonesia, 2017)
Article 21 Income Tax is a tax levied on personal income in the country in the form of salaries, honoraria, allowances and other payments. Objectives Job Training is namely to examine the implementation Overview Against Calculation, Deposit and Reporting of Tax Article 21 Permanent Employee Salary Up, On Ackira Cira Perkasa PT East Jakarta City which is located Rukan Business Park Kirana Kirana Cawang Rk. No. 23 & 25 JL. D. I. Panjaitan Kav. 48. Pursuant to Article 21 Paragraph 1 of Law No. 36 Year 2008 on Income Tax, the parties are obliged to withhold income tax under Article 21 is the employer, in this case Ackira Cira Perkasa PT East Jakarta City, Based on the analysis and discussion of the calculation procedure, deposit and reporting of annual tax return Tax Article 21 for an individual taxpayer, it can take several conclusions, namely: That PT. Cira Ackira Perkasa had done the calculations, reporting in accordance with the Tax Act 36 of 2008 and Per 32 / PJ / 2015 which applies except for the remittance is delayed.Keywords : Tax Payment (SSP), Value Added Tax